Damage analysis and grading control technology of surrounding rock in high geo-stress roadway - Chongyan, Liu; Guangming, Zhao; Cheng, Pan; Xiangrui, Meng; Wensong, Xu; Wenjie, Liu (Scientific reports, 2025)
To investigate the failure mechanism and establish stability control methods for surrounding rock in high geo-stress roadways, this study incorporated the brittle failure characteristics of the surrounding rock mass into a unified strength criterion, developing an elastic-plastic theoretical model to represent rock damage and fracture. Using this model, analytical expressions for the damage rupture radius and stress field distribution are derived, leading to the proposal of a grading control method. The analysis of calculation examples reveals that an increase in stress, damage degree, and the brittleness coefficient of the rock mass results in the expansion of both the plastic damage and damage residual zones. Conversely, an increase in the intermediate principal stress coefficient and support resistance reduces the extent of these zones. The proposed grading control strategy includes three levels: Level I focus on preventing cracks through initial support, Level II involves reinforcing anchor injections to reduce cracks, and Level III applies local borehole pressure relief. Implementing this strategy can significantly reduce stress concentration and deformation in the surrounding rock, providing valuable insights for roadway support control.